Evaluation of the measurement properties of the Perceived Stress Scale (PSS) in Hispanic caregivers to patients with Alzheimer's disease and related disorders. (21st September 2020) - Teresi, Jeanne A.; Ocepek-Welikson, Katja; Ramirez, Mildred; Kleinman, Marjorie; Ornstein, Katherine; Siu, Albert; Luchsinger, Jose
ABSTRACT: Objectives: The Perceived Stress Scale (PSS) is the most widely used measure of perceived stress; however, minimal psychometric evaluation has been performed among Hispanic respondents, and even less among Hispanic caregivers to persons with Alzheimer's disease and related disorders (ADRDs). Design: Secondary data analysis. Setting: New York City, NY, USA. Participants: A sample of 453 community dwelling Hispanic caregivers to patients with ADRD. Measurements: Latent variable models were used to evaluate the PSS. Exploratory and confirmatory factor analyses were used to examine unidimensionality. Differential item functioning (DIF) was examined for age, education, and language using the graded item response model. Results: The factor and bifactor analyses results supported essential unidimensionality of the item set; however, positively worded items were observed using response item theory to be less informative than the negatively worded items. Reliability estimates were high. Salient DIF was not observed for age, education, or language of interview using the primary DIF detection method. Sensitivity analyses using a second DIF detection method identified uniform language-DIF for the item, "In the last month, how often have you felt that you were on top of things?" However, the non-compensatory DIF value was below the threshold considered salient. Conclusions: In summary, the 10-item PSS performed well in a sample of English- and Spanish-speaking Hispanic caregivers to patients with ADRD. Very little DIF, and none of high magnitude and impact, was observed. However, the negatively worded items, perhaps because they are more directly reflective of stress, were more informative. In the context of a short-form measure or computerized adaptive test, more informative items are those that would be selected for inclusion.